Pengaruh Kualitas Produk, Kualitas Pelayanan dan Harga terhadap Kepuasan dan Loyalitas Konsumen - Amran Hotman Saragih; Eko Deswin Siringo-ringo; Firinta Togatorop; Stevanie Tanjaya (Jesya (Jurnal Ekonomi dan Ekonomi Syariah), 2020)
This study aims to determine whether the price and service quality affect consumer purchasing decisions GEPREK BENSU Pematangsiantar and analyze the most dominant factors in influencing consumer purchasing decisions GEPREK BENSU Pematangsiantar. The data collection methods used in this research are questionnaires, interviews and observations. The population in this study was 40 people and the number of samples in this study was 40 people because the sampling in this study used the census method. The data analysis technique used was the instrument test, namely the validity test and the reliability test, the classic assumption test, namely the normality test and the hypothesis test, namely multiple linear regression, the correlation coefficient, the determination coefficient, the partial test (t-test) and simultaneous test (f test). The results showed that price and service quality had a positive and significant effect on purchasing decisions. Based on statistical data analysis, the indicators in this study are valid and the variables are reliable. The author's suggestion is to improve consumer purchasing decisions can be done by way of competitive pricing, increasing product diversity, and improving the quality of service. GEPREK BENSU Pematangsiantar needs to maintain the elements that have been assessed as good (price and quality of service) by customers and need to fix things that are still considered lacking.